KINERJA PENDIDIKAN DASAR DALAM IMPLEMENTASI PROGRAM PENDIDIKAN UNTUK SEMUA - Ismanto, Bambang; Tagela, Umbu; Wasitohadi, Wasitohadi (Universitas Kristen Satya Wacana, 2017)
This research aims to analyze the work performance of elementary schools in Salatiga in achieving the target of MDGs. This research is done with descriptive quantitative method, and measured with the target achievement of 9 year compulsory learning. The analysis is based on the work performance in percentage. The data collection was done in documents studies of the report from the educational report of Salatiga City and Central Java Province, and also through FGD. The result showed that the government of Salatiga City had been successful in executing the 9 year compulsory learning for children of 7-12 years old. In 2015, the APM of the elementary schools was 99,58%,TheAPK was 115,89%. The APM in middle school was 94,22%, and the APK was 129,01%. The number of literate people in 2015 was 99,97%. The gender equity reached the balance point in every grade of education. In order to improve quality, the city has been doing the certification and qualification program for the teachers. The problems that need priority for solution are operational support increase from Revenue and Expenditure Budget, the need to increase the number and the quality of elementary teachers, and equal distribution of inclusive education. This research recommends the Salatiga City government to plan for a quality-based elementary education program, and support sustainable development goals( (SDGs).